Kinetic Monte Carlo simulations of co-deposition of indium and tin on silicon (100)-2x1 surface investigation of chemical selectivity and dimer ordering phenomena - Putungan, Darwin Barayang
The emergence of one-dimensional atomic wires through co-deposition of In and Sn on Si (100)- 2x1 surface was investigated by means of Kinetic Monte Carlo (KMC) simulations. An atomistic lattice gas model incorporating key features (such as C-type defect mediated nucleation,anisotropy of the surface with regards to diffusion and reversible atomic wire growth) pertaining to one-dimensional atomic wires growth through co-deposition was developed, and the corresponding Bortz-Kalos-Liebowitz (BKL) algorithm for the model was implemented.Experimental observations on the co-deposition are scarce and the lack of dimer ordering among the atomic wires were considered in the simulations. Through KMC simulations, it was shown that mix In-Sn dimmers pair-interaction energy is negatively valued. This gave rise to mixed In-Sn dimers' inability and thus creating chemical selectivity. On the other hand, ordering was not induced for cases where the pair - interaction energy of the defect-bound odd-sized atomic wires is equal, less or greater than the pair-interaction energy of defect-bound combined odd-sized atomic wires.Furthermore, dimer ordering was found out to be dependent on the atomic species being deposited since ordering can be induced by making the pair-interaction energy of the defect-bound odd-sized atomic wires to be considerably small. This explained why ordering cannot be induced in the co-deposition experiment of In and Sn since they give rise to defect-bound odd-sized atomic wires whose activation barrier is considerably large.